2013
DOI: 10.1017/s1473550413000232
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in Fe/Mn films, sulphate crusts, and aluminium glazes from Swedish Lapland: implications for astrobiology on Mars

Abstract: Rock coatings have been observed on Mars by Mars Pathfinder, Viking and the Mars ExplorationRovers. Although rock varnish has been studied for its potential as a biosignature, other types of rock coating have been largely ignored. In Kärkevagge, Swedish Lapland, sulphate crusts, aluminium glazes and Fe/Mn films occur with mineralogies mimicking those observed on the surface of Mars. Molecular analysis and scanning electron microscopy (SEM) were used to investigate the bacterial communities associated with thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 120 publications
(209 reference statements)
0
4
1
Order By: Relevance
“…High Fe concentration may explain the lower diversity values for the Fe films in Kärkevagge. When compared to an earlier study in Kärkevagge by the authors using clone libraries, Al glazes, not sulfate crusts, were most diverse, although Fe films were also found to be the least diverse (Marnocha & Dixon, ). Simpson's diversity indices ( D ), where lower values for D mean higher diversity, match well with the Shannon index values.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…High Fe concentration may explain the lower diversity values for the Fe films in Kärkevagge. When compared to an earlier study in Kärkevagge by the authors using clone libraries, Al glazes, not sulfate crusts, were most diverse, although Fe films were also found to be the least diverse (Marnocha & Dixon, ). Simpson's diversity indices ( D ), where lower values for D mean higher diversity, match well with the Shannon index values.…”
Section: Discussioncontrasting
confidence: 54%
“…Pyrosequencing yielded a significant increase in diversity coverage when compared to the Sanger sequencing of our previous investigations (Marnocha & Dixon, ). In comparison with similar environments, the bacterial diversity of rock coatings observed in the valley is relatively high.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Sulfate-rich precipitates are frequently noted in a variety of Antarctic contexts from weathering rinds to rock coatings [74,79,107], in the Swedish Lapland [121], and it has been suggested that sulfate plays a role in barium's behavior in rock varnish [122], sometimes being enriched and correlated with Mn and sometimes not being present in anything other than very minor amounts [123]. Thus, the presence of a strong S-peak in the bacterial sheath observed in Greenland (Figure 7d) should not be surprising.…”
Section: Nanoscale Observations Of Rock Coatingsmentioning
confidence: 99%
“…Some authors have suggested that abiotic processes are sufficient to explain the Mn oxidation and deposition (Collins and Buol, 1970;Elvidge and Iverson, 1983;Goldsmith et al, 2014;Perry et al, 2005;Thiagarajan and Lee, 2004). On the contrary, there is a large body of evidence that suggests an involvement of microorganisms (bacteria or fungi) in the oxidation and precipitation of Mn (Dorn et al, 2013;Gadd, 2017;Jones, 1991;Krinsley et al, 2012Krinsley et al, , 2017Krumbein and Jens, 1981;Kuhlman et al, 2006Kuhlman et al, , 2008Laudermilk, 1931;Marnocha and Dixon, 2013;Wang et al, 2011). The lack of microfossils (Macholdt et al, 2015(Macholdt et al, , 2017b and of evidence for the presence of activated Mnoxidizing enzymes in varnish (Lang-Yona et al, 2018) does not rule out a bacterial role in Mn precipitation, considering the length of time involved in its formation (Dorn and Krinsley, 2011;Krinsley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%